Academic Freedom Movement in Southeast Asian: Threat, Challenge, and It’s Implication in Indonesia - Satria Unggul Wicaksana Prakasa (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2024)
This research focused on analyzing the debates and roles of academic freedom movement in Southeast Asian. The dynamics of protection related to academic freedom cannot be separated from its protection on the one hand and the threats accompanying it. The issue of academic freedom creates a threat to the academic community in producing knowledge, both within universities and those who are active as independent researchers, especially in Southeast Asian. Authoritarianism, in turn, has affected the worse situation of free expression, including academic freedom. In the current situation, the digital sphere has been targeted as well. This article will discuss the following questions: (1). What is the situation of the academic freedom movement and protection for the academic community in Southeast Asia? (2). How are efforts to maintain the movement of academic freedom in Southeast Asia, especially in Indonesia, amid efforts to subjugate the campus by the state and the practice of authoritarianism? Using an interdisciplinary approach as a part of socio-legal research, this article argued that there is a strong relationship between the threat of academic freedom movement in Southeast Asian countries and the implications in Indonesia. The academic freedom situation in Southeast Asia has been shaped by the political and economic aspects of the region as well as in their respective countries. The role of independent and progressive alliances to struggle for their rights or to understand the role of professor unions in defending academic and scientific freedom. To what extent is academic freedom considered a strong pillar for democratic societies, including providing important scientific, economic, cultural, and social progress from which we may all benefit? This roundtable is also aimed to promote possible strategies in challenging democracy declines, affecting the shrinking civic space, and how academic resilience in the digital space is a keyword that should be strengthened in its social movement since this will be more complicated due to manipulating information and anti-science politics through systematic repression.